2021
DOI: 10.1002/lary.29843
|View full text |Cite
|
Sign up to set email alerts
|

Oral Somatosensory Sensitivity in Patients With Taste Disturbance

Abstract: Objective The significance of the human sense of taste is typically underestimated until it is altered or even lost. Hypogeusia, a diminished capacity to taste, has an adverse influence on a patient's quality of life. Similar to interactions between the oral senses and between olfaction and intranasal trigeminal sensitivity, taste disturbance may also affect the mechanosensitivity of the tongue. In this study, we investigated the lingual tactile sensitivity of patients with subjective taste disturbance and peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In this study, patients self-reported a taste disturbance, and a lower astringent sensitivity, that might reflect a generalized impairment also in the somatosensory function. Bogdanov and colleagues demonstrated that patients with taste impairments had lower acuity also in their somatosensory sensitivity in a 3D-letter identification test [ 32 ], which was correlated with fungiform papillae density [ 30 ], whereas in another study, texture acuity was higher in subjects with high sensitivity for the bitter compound 6-n-propylthiouracil (PROP) [ 49 ]. Additionally, the intensity of astringency was rated as lower in PROP non-sensitive subjects according to gender [ 50 , 51 ] which are known to have lower density of fungiform papillae in the anterior two-thirds of the dorsal tongue surface and lower taste sensitivity compared to the sensitive phenotype [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, patients self-reported a taste disturbance, and a lower astringent sensitivity, that might reflect a generalized impairment also in the somatosensory function. Bogdanov and colleagues demonstrated that patients with taste impairments had lower acuity also in their somatosensory sensitivity in a 3D-letter identification test [ 32 ], which was correlated with fungiform papillae density [ 30 ], whereas in another study, texture acuity was higher in subjects with high sensitivity for the bitter compound 6-n-propylthiouracil (PROP) [ 49 ]. Additionally, the intensity of astringency was rated as lower in PROP non-sensitive subjects according to gender [ 50 , 51 ] which are known to have lower density of fungiform papillae in the anterior two-thirds of the dorsal tongue surface and lower taste sensitivity compared to the sensitive phenotype [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, capsaicin, which is the main trigeminal-activating compound in chili pepper [ 29 ], is applied to elicit the burning sensation of spiciness. Recently, oral tactile acuity was shown to be positive correlated to the density of fungiform papillae [ 30 , 31 ], and to be lower in patients with taste dysfunction compared to a control group [ 32 ], suggesting that impairments in taste have an impact on trigeminal sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…In systemic diseases with taste dysfunction involvement, there is commonly a misconception that this symptom is secondary to other complications of the disease such as oral dryness, microbiome dysbiosis, or decline of central processing. However, as knowledge of how taste signals are processed and more accurate tests to test the same have developed, the nature of taste loss in various systemic diseases has come under renewed interest ( 296 – 298 ). Two tests being utilized to decipher distinct involvement of the peripheral gustatory apparatus are the taste strip tests (TST) to measure taste responses in different regions of the tongue ( 299 ) and the electrogustometer (EGM) to measure peripheral neuronal activation ( 300 ).…”
Section: Diseases Of the Tongue And Systemic Diseases That May Be Ref...mentioning
confidence: 99%
“…It is thought to be a consequence of the deposition of abnormal protein aggregates such as alpha-synuclein in olfactory bulbs ( 314 ). Taste impairment in PD has not been as well documented as taste disturbances are often considered secondary to hyposmia ( 296 , 315 ). In one longitudinal study, taste impairment, though stable, was a persistent finding based on TST.…”
Section: Diseases Of the Tongue And Systemic Diseases That May Be Ref...mentioning
confidence: 99%
“…Mastinu and coauthors showed that sweet taste was the taste sensation most frequently identified correctly, followed by salty taste, bitter taste, and sour taste, and that patients with taste impairments had lower identification scores for astringency (a sensation of dryness) and spiciness (a burning sensation). These correlations suggest a connection at a peripheral level between the gustatory and somatosensory perceptions [ 39 , 40 ] that sometimes fail after skull base surgery [ 41 , 42 ]. On the other hand, these results suggest that taste perception, and especially taste dysfunction, are complex and governed by numerous factors.…”
Section: Introductionmentioning
confidence: 99%